Cochrane Database of Systematic Reviews 2008
DOI: 10.1002/14651858.cd005381.pub3
|View full text |Cite
|
Sign up to set email alerts
|

Physical activity and enhanced fitness to improve cognitive function in older people without known cognitive impairment

Abstract: Take-down policy If you believe that this document breaches copyright please contact us providing details, and we will remove access to the work immediately and investigate your claim.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

35
604
2
19

Year Published

2009
2009
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 791 publications
(660 citation statements)
references
References 70 publications
35
604
2
19
Order By: Relevance
“…Intervention (Kramer et al 1999;Renaud et al 2010b;Langlois et al 2012) as well as cross sectional (Renaud et al 2010a;Boucard et al 2012;Berryman et al 2013) and longitudinal (Yaffe et al 2001;Barnes et al 2003;Larson et al 2006) studies suggest that higher physical fitness levels are associated with better cognitive functions. Different review articles and meta-analyses of intervention studies also support these results, which tend to confirm the beneficial effects of physical activity on cognitive functions and mental health in older adults (Smith et al 2010;Colcombe and Kramer 2003;Hillman et al 2008;Voss et al 2011;Angevaren et al 2008;Matta Mello Portugal et al 2013). Moreover, it seems that physical fitness has a selective enhancing effect on executive functions (Kramer et al 1999;Colcombe and Kramer 2003;Smiley-Oyen et al 2008).…”
Section: Introductionmentioning
confidence: 77%
“…Intervention (Kramer et al 1999;Renaud et al 2010b;Langlois et al 2012) as well as cross sectional (Renaud et al 2010a;Boucard et al 2012;Berryman et al 2013) and longitudinal (Yaffe et al 2001;Barnes et al 2003;Larson et al 2006) studies suggest that higher physical fitness levels are associated with better cognitive functions. Different review articles and meta-analyses of intervention studies also support these results, which tend to confirm the beneficial effects of physical activity on cognitive functions and mental health in older adults (Smith et al 2010;Colcombe and Kramer 2003;Hillman et al 2008;Voss et al 2011;Angevaren et al 2008;Matta Mello Portugal et al 2013). Moreover, it seems that physical fitness has a selective enhancing effect on executive functions (Kramer et al 1999;Colcombe and Kramer 2003;Smiley-Oyen et al 2008).…”
Section: Introductionmentioning
confidence: 77%
“…This conclusion was also reached by cognitive health researchers reviewing evidence from epidemiology, animal models and randomized studies in humans (Albert et al, 2007). In the area of physical activity, evidence from epidemiology and animal models is increasingly strong (Hendrie et al, 2006;Cotman and Berchtold, 2007), while evidence from randomized interventions in humans remains mixed (Colcombe and Kramer, 2003;Heyn et al, 2004;Angevaren et al, 2008;van Uffelen et al, 2008). The American College of Sports Medicine (ACSM) recently concluded that cardiovascular fitness and higher levels of physical activity reduce the risk of cognitive decline and dementia, and that physical activity in previously sedentary older adults can improve cognitive performance, particularly for complex tasks requiring executive control (Salem et al, 2009).…”
Section: Resultsmentioning
confidence: 99%
“…Thus, we anticipated that supervets would show smaller costs in carrying a PM intention, based on the evidence that exercise increases attentional resources used for monitoring (Barnes et al, 2003;Voss et al, 2010;Angevaren et al, 2008, Smith et al 2010Erikson et al, 2011;Winker et al, 2010;Voss et al, 2010a). In contrast, in both tasks, supervets showed greater cost in carrying a PM intention.…”
Section: Memorymentioning
confidence: 99%